Analisis Dampak dan Tindakan Pencegahan Bullying Dikalangan Pelajar dalam Persepsi Hak Asasi Manusia - Karimah, Natiqatul; Jayanti, Olyvia Syafira Putri; Astari, Marsyadini; Nurhasanah, Nurhasanah (Indo-MathEdu Intellectuals Journal, 2024)
Bullying is any form of oppression or violence, which is done deliberately by a stronger person or group to intimidate or dominate others who are perceived as weaker. Both physical, verbal, and nonverbal bullying (spicy). Bullying often occurs in the school environment. This study uses a literature study study method. The main source of this research is research articles published on various sources, namely Google Scholar, Scopus, and Web of Science. The keyword used in literary livelihood is "bullying". The dtaa analysis was carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. The findings of this study are that bullying has a huge impact on the victim's mental health, confidence, the victim feels depressed and will even injure himself or commit suicide. Indonesia is a country of law and human rights cannot be violated because human rights are highly respected. By protecting human rights, the goal is to prevent bullying behavior and minimize human rights violations. This study aims to determine the impact and prevention of bullying among students on the perception of human rights